Improvements and Future Challenges for the Research Infrastructure in the Field of "Preschool Education" - C. Katharina Spiess (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Given the importance of the early stage of a child`s life and taking into account that there various initiatives underway to improve preschool programs in German, it is remarkable that there are only a few microdatasets covering the field of preschool education in Germany - even less if the focus is on nationally representative datasets. The majority of these at least provide information on attendance of preschool programs. In principle there are two main groups of data: data that comprise part of the official statistics and survey data. However, there are hardly any data which allow a linkage between preschool program information and child outcome data. Furthermore, better data for children up to three years are needed, as well as data for children from migrant families. In particular, there is a need for good panel data allowing to match individual data and institutional information Given the developments in the German data infrastructure, the potentials for preschool education research will certainly improve. Nevertheless there remain a number of gaps. Among the mentioned recommendations the paper recommend improvements in fields, such as better data on the quality of preschool programs, better data on the family context and the costs of preschool education and finally the paper addresses the need for detailed intervention studies (on a representative (generalizable) level, which help to learn more about the most effective and efficient parameters of preschool programs.
Keywords: 330; preschool education; day care; child outcomes